Predictors of health behaviors and cardiovascular disease risk factors for professional firefighters - Dussinger, Beth, author; Nelson, Tracy, advisor; Lipsey, Tiffany, committee member; Graham, Dan, committee member (Colorado State University. Libraries, 2014)
Although the leading cause of mortality among all Americans is cardiovascular disease (CVD), accounting for about 32% of deaths, the risk among firefighters is even higher. About 45% of on-duty firefighter deaths result from CVD. While their strenuous job duties most often precipitate the CVD-related events, almost all of these incidents are occurring in firefighters with underlying risk factors for CVD. Health behaviors such as diet and exercise are known to have large impacts on known CVD risk factors; however, the dietary habits of firefighters have not been extensively studied. Also the impact of various work-related factors on diet and exercise has not been quantitatively documented. Therefore, the purpose of this cross-sectional study was to elucidate the association between health behaviors and CVD risk factors among firefighters and to analyze predictors for these health behaviors including call volume, social norms and other factors associated with the fire station environment. Subjects included 42 professional firefighters (mean age 41.0 ± 9.6 years, 95.2% male) who participated in the Heart Disease Prevention Program (HDPP) at Colorado State University. These evaluations provided data on body fat percentage, body mass index, waist circumference, blood pressure, blood lipids, C-reactive protein, cardiorespiratory fitness, overall coronary risk, and records of on-duty and off-duty diet. These individuals and 40 more Colorado firefighters (mean age 41.0 ± 8.7 years, 92.5% male) completed a questionnaire on motivations for health behaviors. Of these 82 firefighters, 46 completed an on-line dietary screener. Most participants displayed risk factors for CVD, including increased rates of obesity, systolic blood pressure, and triglycerides. Diet records also showed reason for some concerns and correlation with CVD risk factors. Firefighters reported consuming about 37% of their daily calories from fat. Diet records showed sodium intake of 65% more than the tolerable upper level (UL) and fiber intake 25% lower than the adequate intake level (AI). The American Heart Association goals were met for fruits and vegetables by about 26% of participating firefighters, for whole grains by about 28%, for sugar-sweetened beverages by about 35%, for sodium by 0%, and for physical activity by 43%. Sodium intake was positively correlated with systolic blood pressure (SBP) (p<.05) and physical activity was negatively correlated with SBP (p<.05). Increased consumption of added sugar showed correlation with increased body fat percentage, triglycerides, and overall coronary risk (p<.05). The volume of emergency calls showed minimal association with CVD risk factors, diet and exercise. Aspects of social norms and group cohesion appeared to have some correlation with diet and exercise behaviors. Convenience and the availability of unhealthy snacks at the fire station were commonly reported and showed associations with the diet. Emotional eating cues and cost were not shown to be strongly related to eating habits. Certain family and home environment factors appeared to also be strongly connected with health behaviors. In conclusion, these findings suggest there are work-related predictors of health behaviors and CVD risk for firefighters, but the home environment showed associations with health behaviors, too.
Keywords: call volume; convenience; diet; firefighter; physical activity; social norms